From the Natural Self-Orgnizaton of Religion to the Modern Magical Realism of the Religious Experience - Gerardo Abreu Pederzini (Academicus, 2019)
Religion is a powerful phenomenon arising in and from society. Various efforts have been done to understand religion as a natural phenomenon, which could be framed in the language of science. In this paper, I forward a sui generis approach to the naturality of religion, where religion is explained as one of the next stages in broader natural processes of self-organization. Furthermore, having framed like this the naturality of the religious experience, the paper explores the contemporary debate of current religious expressions. It is suggested that the arrival of science and the modern society have changed some expressions of religious experiences; while, nonetheless, keeping their capacity to self-organize societies. The magical realist society, as the society capable of disguising the magic of religion within the realism of the scientific ethos, is presented and discussed as a modern secular expression of religion, capable to cope with the challenges of science through the dynamics of modernity and capitalism.